The Long-Term Effect of Cancer on Incident Stroke: A Nationwide Population-Based Cohort Study in Korea - Jang, Hyun-Soon; Choi, Jimi; Shin, Jaewon; Chung, Jong-Won; Bang, Oh Young; Kim, Gyeong-Moon; Seo, Woo-Keun; Lee, Juneyoung (Frontiers in Neurology, 2019)
Background and Purpose: Despite the recent growing interest in the cancer–stroke association, the long-term effect and organ-specific association with stroke incidence in subjects with cancer have not been clearly defined. Methods: Data were obtained from the Korean National Health Insurance Service National Sample Cohort database between 2002 and 2015. To investigate the effects of cancer on stroke incidence, subjects were classified into cancer and non-cancer groups based on the period after cancer diagnosis and origin organ of cancer. To minimize the effects of selection bias, we performed a propensity score matching analysis with covariates of demographic data, vascular risk factors, antithrombotics use and statin use. Incident stroke was diagnosed based on operational definition and classified into ischemic stroke and hemorrhagic stroke. Results: Data of 20,707 subjects with cancer and 675,594 without cancer were analyzed for 7 follow-up years. The subjects with cancer had higher risk of any stroke (subdistribution hazard ratio [SHR], 1.13; 95% confidence interval [CI], 1.02–1.26; p = 0.0181) than those without cancer. Similar trend was found for ischemic stroke (SHR, 1.17; 95% CI, 1.05–1.31; p = 0.0054), but not for hemorrhagic stroke. The risk of stroke was increased in subjects with cancer in the digestive organ, respiratory and intrathoracic organ, and “others (such as breast and female and male reproductive organs)” for 3 years; however, the association disappeared thereafter except those with “others” cancer. Chemotherapy increased the risk of ischemic stroke (SHR 1.21; 95% CI, 1.03–1.41). Conclusions: Cancer increases the risk of stroke at 3 years after the diagnosis of cancer, and the effect was maintained for 7 years. The association between cancer and stroke incidence depends on the organ from which the cancer originated and chemotherapy.